2014
DOI: 10.3857/roj.2014.32.4.238
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of high-dose-rate interstitial brachytherapy in patients with oral cavity cancer

Abstract: PurposeTo evaluate the clinical outcome of high-dose-rate (HDR) interstitial brachytherapy (IBT) in patients with oral cavity cancer.Materials and MethodsSixteen patients with oral cavity cancer treated with HDR remote-control afterloading brachytherapy using 192Ir between 2001 and 2013 were analyzed retrospectively. Brachytherapy was administered in 11 patients as the primary treatment and in five patients as salvage treatment for recurrence after the initial surgery. In 12 patients, external beam radiotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Kakimoto et al indicated 71% three-year local control in T3 mobile tongue cancers with definitive HDR-BT [ 22 ]. In patients with definitive HDR-IBT, Lee et al showed five-year overall survival and three-year local control of 70% and 84%, respectively [ 23 ]. As evident, our outcomes are in agreement with the other reports despite the extensive variety in patient characteristics and treatment composition of surgery, external radiotherapy, and brachytherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Kakimoto et al indicated 71% three-year local control in T3 mobile tongue cancers with definitive HDR-BT [ 22 ]. In patients with definitive HDR-IBT, Lee et al showed five-year overall survival and three-year local control of 70% and 84%, respectively [ 23 ]. As evident, our outcomes are in agreement with the other reports despite the extensive variety in patient characteristics and treatment composition of surgery, external radiotherapy, and brachytherapy.…”
Section: Discussionmentioning
confidence: 99%